EFEKTIVITAS MEDIA PEMBELAJARAN DIGITAL BERBASIS GAME (WORDWALL) TERHADAP MINAT BELAJAR DAN PEMAHAMAN KONSEP SEJARAH PADA KELAS X SMK MADINATUL ULUM - Rofik; Adzkiyak; Ma`ruf Wijaya, Agi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
In history subjects, learning challenges often arise because historical material is identical to memorizing figures, dates, and events. This condition causes some students to consider history as a boring lesson, resulting in low interest in learning and low understanding of learning concepts. The purpose of this study is to observe the learning process before the application of game-based digital media (wordwall), then to analyze the effectiveness of the application of game-based digital learning media (wordwall) on the learning interest of class X students of SMK Madinatul Ulum and to analyze the effectiveness of the application of game-based digital learning media (wordwall) on the understanding of concepts of class X students of SMK Madinatul Ulum. This research method uses an approach in this study using quantitative with experimental methods and Pretest-Posttest Cointroil Group Design. The research stages include preliminary studies, instrument preparation, pretest implementation, treatment administration, posttest, and data analysis using normality, homogegeneity, and independent samples t-test tests. The research sample consisted of an experimental class using Educaplay and a control class using conventional learning. The results showed that game-based digital learning media (wordwall) influenced the learning interest and understanding of learning concepts of 10th-grade students at SMK Madinatul Ulum.